An assessment of the reliability of financial reports of listed Philippine banks and holding companies - Cayanan, Arthur S.; Echanis, Erlinda S. (Quezon City College of Business Administration, University of the Philippines Diliman, 2006)
This study shows the results of the assessment of the financial reporting practices of listed Philippine banks and holding companies as regards to their compliance with the generally accepted accounting principles in the Philippines. The study shows as well the common characteristics of companies whose noncompliance with the financial reporting rules resulted in any of the following: overstatement of revenues, overstatement of assets, understatement of expense, and understatement of liabilities. To determine the common characteristics of the companies which did not comply, logistic regression was performed. the following variables were initially considered to explain the common characteristics of companies which failed to comply with finanacial reporting standards: being regulated; debt ratio; income taxes/revenues ration; total assets; float. the Study also includes an assessment of the adequacy of financial reporting rules applicable to banks and holding companies. The study covers 152 annual reports from the 79 listed companies composed of 17 banks and 62 holding companies. The 17 banks represent 100% of the listed Philippine banks as of 2003 while the 62 holding companies represent 95% of the listed holding companies also of the same year. Of the 152 annual reports, 55 observations of noncompliance were noted which resulted in the misstatement of assets, liabilities, earnings, and expenses. The logistic regression showed that being regulated and debt ratio are statistically significant even at 99% confidence level in determining which companies would most likely not comply with reporting rules. Other individual financial reporting violations are described in this study.
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Financial statements -- Philippines; Financial institutions -- Accounting. -- Philippines; Banks and banking -- Accounting. -- Philippines